The challenges of IFRS 9 standard reform Case: Company X - Häikiö, Merika (My University, 2017)
This thesis focuses on the challenges the case company, a Finnish financial institution, has experienced during the implementation process of IFRS 9 standard reform. The thesis follows the IFRS 9 gap analysis -project at Company X, during the fall of 2016. The objective of the study is to increase knowledge and understanding about the implementation processes of IFRS standard reforms and how the challenges can be managed. There is very little qualitative research about IFRS standards. The theoretical framework is based on previous studies about the initial IFRS implementation process in 2005. Additionally, guidelines provided by the IASB and the Big 4 consulting agencies are used. This is a qualitative case study that applies content analysis method. Interviews with 3 project team members, observation and written materials from the case company were used to collect the data. For Company X, the most significant challenges in the ongoing implementation process can be categorized as internal and standard related challenges. Internal challenges included limited resources, difficulties with communication as well as with gathering and analyzing data. In addition, the company has experienced challenges related to the standard itself, such as the complexity of the standard as it requires exercising own judgment. The possible effects the standard has on financial reporting and more widely on the business were considered challenging. However, several of these challenges were already solved with the help of the ongoing IFRS 9 project and the use of IFRS experts as consultants.
Keywords: IFRS; IFRS 9; financial instruments; implementation; challenges; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|